"IMPROVEMENT OF INFORMATION-COMMUNICATION READINESS OF STUDENTS THROUGH TEACHING THE SCIENCE OF ENGINEERING GRAPHICS" (Intent Research Scientific Journal, 2023)
In this article, in the preparation of future specialists for the activities of engineer-teacher, trainer, master, innovative information-didactic forms of education, methods of automating design processes, pedagogical and technological bases for the integration of technology and information tools into a single system, and the formation of the relevant necessary skills for the formation of the necessary skills in practice imparting knowledge is explained.